ARAB STUDENTS INSIDE THE SOVIET BLOC : A CASE STUDY ON CZECHOSLOVAKIA DURING THE 1950S AND 60S - Daniela Hannova (European Scientific Journal, ESJ, 2014)
The paper focuses on the phenomenon of students from the so-called less developed countries in communist Czechoslovakia, specifically Arab students in the 50s and 60s of the twentieth century. The first part of the paper focuses on a broader political and social context. Because it was the first wave of Arab scholarship holders supported by the Czechoslovak government to arrive at the end of the 50s, it is crucial to describe the shape of negotiations between the Czechoslovak and Arab sides. The second part of the paper emphasizes cultural agreements and types of studying in Czechoslovakia. Arriving abroad, preparatory language courses, everyday life of Arab students in Czechoslovakia and the conflicts they had faced are analyzed in the following subchapters. The problem of Arab student adaptation to the new environment and troubles caused by cultural differences are illuminated in the framework of these thematic sections. The final part of the paper outlines the Arab absolvents’ fates and their contacts with Czechoslovakia after ending their university studies and returning to their homeland.